CAGE15-6 Cruise Report: Arctic gas hydrate studies - Mienert, Jürgen; Hong, Wei-L.; Jansson, Per; Waghorn, Kate A.; Waage, Malin; Singhroha, Sunny; Osti, Giacomo; Yao, Haoyi; Iversen, Steinar; Olsen, Bjørn R.; Heimdal, Karianne; Krokmyrdal, Suchada; et al. (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
RV Helmer Hanssen is the only vessel operating so far north (81 N) in October. One of the research questions addressed during this cruise is: Where do gas hydrate exist in the seabed and how much methane does it actually release? The CAGE 15-6 cruise explored potential gas hydrate charged sub-seabed environments and gas release zones at Storfjordrenna, Vestnesa and Svyatogor Ridge, Yermak Plateau, Sofia Basin and west of Prins Karls Foreland. Our route was traceable by www.sailwx.com. The weather forecasts from www.windyty.comwere used to prepare and adjust our cruise activities. In these Barents Sea-Arctic areas we carried out seismic profiling (mini GI 15/45 in 3 and large GI45/105 in 3) and 6 m long gravity coring for detecting gas hydrate, acoustic profiling (18, 38 and 120 kHz) for detecting gas flares in the water column, and CTD water sampling for gas analyses. Multibeam bathymetry mapping (EM300) data was collected on route for the entire cruise. We also ran echo sounder profiles along the NW Svalbard margin, across Yermak Plateau from west to east into the Sofia Basin and upslope towards the northern Svalbard margin. We reached the upper gas hydrate stability (GHSZ) theoretical outcrop zone but no acoustic evidence for extended gas release activity was found along the GHSZ outcrop zone at Yermak Plateau. The cruise may be known as: CAGE15_6